The problem of numerical simulation of digital protective relay and its analog–digital (hybrid) solution - Suvorov A. A. Aleksey Aleksandrovich; Andreev M. V. Mikhail Vladimirovich; Askarov A. B. Alisher Bakhramzhonovich; Kievets A. V. Anton Vladimirovich (2020, 2020)
Title screen